PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DIAGNOSA COFFEE & SPACE - Ashillah Azizah; Dian Sudiantini, Aulia Khuswatun Hasanah, Muhammad Abdullah Husein, Salsa Paulina Rahman, Selviyansy (ADISAM PUBLISHER, 2024)
The aim of this research is to analyze the influence of Brand Image and Product Quality on the Purchase Decision at Diagnosa Coffee & Space, as well as to find out which variables are most dominant in the decision to purchase coffee at Diagnosa Coffee & Space. The research method used is qualitative, using primary data sources. Data collection methods were obtained by observation and interviews. The research results show that brand image and product quality variables influence purchasing decisions for Diagnosa Coffee & Space products.